PERAN STRATEGI PEMASARAN BERBASIS INFORMATION COMMUNICATION AND TECHNOLOGY (ICT) DALAM MENINGKATKAN PENJUALAN PRODUK UKM - Haryadi, Wahyu; Nursadita, Fidya (Samalewa: Jurnal Riset & Kajian Manajemen, 2025)
This study aims to know the role of information communication and technology (ICT) based marketing strategy on increasing sales of SME products in Sumbawa District. The type of this study was associative study aimed to examine the effect of information communication and technology (ICT) based marketing strategy on increasing SME product sales in Sumbawa District. The type of data used in this study was quantitative obtained directly from primary sources using a research instrument in the form of a questionnaire. Respondents in this study were 85 MSME actors in Sumbawa District. Determination of respondents in this study using probability sampling techniques with the simple random sampling method. The data processing tool used the SPSS version 16.0 for Windows application to be analyzed using simple linear regression analysis techniques, partial hypothesis testing (t-test), and coefficient of determination testing (R2). The results of this study showed that ICT-based marketing strategies had a positive and significant effect on sales of SME products in Sumbawa District. The ability of the ICT-based marketing strategies to effect on sales of SME products in Sumbawa District was 73.6%, while the remaining of 26.4% was effected by other factors not examined in this study, such as price, promotion, product and service.